International responsibility for breaching the principle of prohibition of the use or threat of force and the extent of its impact on contemporary international relations (A descriptive analytical study) - Abdelmagead, Abker Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The importance of the study stemmed from explaining the mechanisms for activating the principle of prohibiting the use or threat of force to show the extent of the effectiveness of these mechanisms in changing contemporary international relations, and their adequacy in achieving global peace and security, protecting the principle of state sovereignty, and the means available to the international community to confront aggression and the threat of force in light of the transformations Contemporary international law, the main problem of the study revolves around clarifying the implications of violating the principle of prohibiting the use of force, and the international legal mechanisms to limit aggression and protect the sovereignty of states. The study aimed to know Russia's international responsibility for violating international principles in its war on Ukraine, the extent of the legitimacy of the referendum it conducted on the regions of Luhansk, Zaporizhia, Kherson, and Donetsk according to the rules of public international law, and the position of the international community towards it. The study followed the analytical descriptive approach, the inductive approach, and the historical approach. The study reached a number of results, the most important of which is that the principle of prohibiting the use or threat of force in contemporary international relations has been shaken and does not constitute any binding legal force, especially in the Russian aggression against Ukraine. The study came out with several recommendations, the most important of which is to reconsider the formation of the Security Council by increasing the number of permanent members and not giving the right of veto any effect in the event of a threat to international peace and security or the occurrence of aggression.
Keywords: Violation; prohibition of force; threat; international relations